2008
DOI: 10.1007/s11999-008-0660-2
|View full text |Cite
|
Sign up to set email alerts
|

Distal Radius Fractures in Older Patients: Is Anatomic Reduction Necessary?

Abstract: The relationship between radiographic and functional outcomes in older patients with distal radius fractures is controversial. We explored this relationship by assessing the influence of radiographic displacement and fracture comminution on the functional outcomes of these fractures. We also asked whether operative intervention and demographic factors (age, gender, duration of followup) influenced outcome. We examined 53 patients older than 55 years with distal radius fractures with various functional assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 45 publications
8
63
0
5
Order By: Relevance
“…But there is currently no evidence that this anatomical reconstruction is beneficial for the patient's function and pain. Synn et al [19] cited nine studies that showed no beneficial effect on function despite improved radiological results and 11 studies that had better functional outcomes compared with other treatment methods, but all these studies involved elderly patients. Kumar et al [20] found that the QD after 14 months was related to the radiological results in patients under 60 years of age, but not in patients over 60 years of age.…”
Section: Locking Plate Fixationmentioning
confidence: 99%
“…But there is currently no evidence that this anatomical reconstruction is beneficial for the patient's function and pain. Synn et al [19] cited nine studies that showed no beneficial effect on function despite improved radiological results and 11 studies that had better functional outcomes compared with other treatment methods, but all these studies involved elderly patients. Kumar et al [20] found that the QD after 14 months was related to the radiological results in patients under 60 years of age, but not in patients over 60 years of age.…”
Section: Locking Plate Fixationmentioning
confidence: 99%
“…38 However one study 37 did follow-up their participants for 5-6 years, and another 39 for an average of 39 months and although Brogren et al 39 found that there was correlation between malunion and poorer function and pain at 1 year, no such correlation was found in either study at long-term followup. These results, and those of others, 2 could suggest that radiological outcomes in the short-term (3-12 months) may have some effect on function, but in the long-term these effects lose significance.…”
Section: Discussionmentioning
confidence: 97%
“…Reviewing the literature, of the studies looking at elderly populations only, the majority 4,8,34,37,38,41 found no significant correlation between functional outcome and radiological outcome. Studies including patients of all ages were more likely to show some correlation between radiological outcome and function, with authors 2,35,36,40 citing radial shortening and dorsal/volar angulation as having the most significant effect on function.…”
Section: Discussionmentioning
confidence: 98%
“…I åtte studier (29,34,(48)(49)(50)(51)(52)(53)(54) med til sammen 498 pasienter var det ingen sammenheng mellom det røntgenologiske og det kliniske resultatet blant eldre, mens man i én studie (55) …”
Section: Eldre Pasienterunclassified